2021
DOI: 10.3390/geosciences11080343
|View full text |Cite
|
Sign up to set email alerts
|

Nonlinear Dynamic Analysis of a Masonry Arch Bridge Accounting for Damage Evolution

Abstract: This study investigates the nonlinear dynamic response of the masonry bridge ‘Ponte delle Torri’ in Spoleto, aiming at assessing the seismic performance of the structure and evaluating the occurring damaging mechanisms. A 3D Finite Element (FE) macromechanical procedure implemented in the FE program FEAP is adopted to model the bridge. To reproduce the typical nonlinear microcracking process evolving in masonry material when subjected to external loads, an isotropic damage model is used. This is based on a sca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 36 publications
0
3
0
Order By: Relevance
“…Masonry material response is described by the constitutive law with damage proposed in Addessi and Sacco 2016 [4]. This phenomenological law has already been applied in FE analyses of masonry bridges, within a macromechanical approach, as reported in [6,11] where the response of the monumental bridge of Spoleto, in Italy, has been extensively investigated under seismic actions focusing on its damage scenarios. The adopted isotropic law models the damage evolution due to microfracture process related to prevalent tensile states in masonry.…”
Section: Damage Law For Masonrymentioning
confidence: 99%
See 1 more Smart Citation
“…Masonry material response is described by the constitutive law with damage proposed in Addessi and Sacco 2016 [4]. This phenomenological law has already been applied in FE analyses of masonry bridges, within a macromechanical approach, as reported in [6,11] where the response of the monumental bridge of Spoleto, in Italy, has been extensively investigated under seismic actions focusing on its damage scenarios. The adopted isotropic law models the damage evolution due to microfracture process related to prevalent tensile states in masonry.…”
Section: Damage Law For Masonrymentioning
confidence: 99%
“…(4)where is the current damage value evaluated in the basis of the nonlocal equivalent strain measure and several mechanical parameters, for which a more detailed description is reported in [4,11,12]: (5) Damage formulation is also based on the assumption of thermodynamic irreversibility, for which , and the maximum damage state is reached for a value of the scalar variable D equal to 1.…”
Section: Damage Law For Masonrymentioning
confidence: 99%
“…The main focus is on horizontal actions due to seismic phenomena. The dynamic response of the Ponte delle Torri Viaduct and the damage caused by the recent earthquake were investigated in [6]. Cyclic push-over analysis with the effect of natural seismic spectra was carried out in [7].…”
Section: Introductionmentioning
confidence: 99%
“…The investigation showed that the bridge has generated high tensile stress at the spandrel walls which causes the failure of the bridge. Addessi et al (Addessi et al 2021) investigated the bridge response to the sequence of the accelerogram as well as for single record. The study found that the relationship between the damage index and control node displacement is noteworthy and provides the significant information regarding the performance of the bridge.…”
Section: Introductionmentioning
confidence: 99%